Learning to Act on World Trade: Preference Formation of Large Firms in the United States and the European Union - Cornelia Woll (Max Planck Institute for the Study of Societies, 2005)
Lobbying by economic actors constitutes a central element of a large part of the literature on trade policy-making. However, it is mainly considered as 'input' into the political system, which then aggregates the demand of different societal interests. As such inputs, the preferences of economic actors are often simply deduced from economic theory. This paper raises doubts about the usefulness of this analytical parsimony and tries to distinguish more clearly between stable interests, preferences and strategic choices. In particular, it suggests a model that clarifies how abstract interests are translated into concrete policy choices. By examining the lobbying carried out by service providers in the United States (US) and the European Union (EU) in telecommunications and air transport, it then shows that the deduction of trade policy preferences from economic theory does not account well for the general support of multilateral trade liberalization by EU service providers. In particular, changes in identity, causal beliefs and strategic environments in the US and the EU create a variety of lobbying choices that goes beyond the material incentives of trade liberalization. By studying the learning process and the constraints on lobbying imposed by political institutions, the paper suggests that even the political preferences of strong economic actors are sometimes more appropriately dealt with as endogenous to the trade policy process. – – Wirtschaftslobbying ist ein zentraler Bestandteil der Literatur zur Welthandelspolitik, da man davon ausgeht, dass Unternehmen Regierungsstrategien nachhaltig beeinflussen. Lobbying wird daher im Allgemeinen als ?Input? in den politischen Prozess definiert. Unternehmensinteressen bilden einen Teil der ?Nachfrage?, die von Regierungen aggregiert und in politische Entscheidungen umgewandelt wird. Der Inhalt der wirtschaftspolitischen Interessen von Unternehmen wird dann in den meisten Fällen aus der Ökonomischen Theorie abgeleitet. Die Autorin des vorliegenden Discussion Papers hinterfragt die Zweckmäßigkeit einer solchen analytischen Vereinfachung und versucht, Interessen, Präferenzen und strategische Entscheidungen klarer voneinander abzugrenzen. Zu diesem Zweck wird ein Modell vorgestellt, das erklärt, wie abstrakte Interessen in konkrete politische Entscheidungen übersetzt werden. Eine Untersuchung der Lobbying-Praxis von Dienstleistungsfirmen in den Branchen Telekommunikation und Lufttransport in den USA und der Europäischen Union zeigt, dass rein materielle Anreize nicht ausreichen, die politischen Präferenzen von Dienstleistungsunternehmen der EU zu erklären. Neben den wirtschaftlichen Konsequenzen einer multilateralen Öffnung der Weltmärkte sind Identitätswandel, grundsätzliche Überzeugungen und die strategischen Grundbedingungen im jeweiligen Land für die Präferenzbildung der Unternehmen entscheidend. Das Papier kommt zu dem Ergebnis, dass Unternehmenspräferenzen nicht als gegeben angenommen werden können, sondern im Laufe des politischen Prozesses fortentwickelt werden.
Keywords: 300